2005
DOI: 10.1074/jbc.m410420200
|View full text |Cite
|
Sign up to set email alerts
|

Centrosomal P4.1-associated Protein Is a New Member of Transcriptional Coactivators for Nuclear Factor-κB

Abstract: Nuclear factor-B (NF-B) is a transcription factor important for various cellular events such as inflammation, immune response, proliferation, and apoptosis. In this study, we performed a yeast two-hybrid screening using the N-terminal domain of the p65 subunit (RelA) of NF-B as bait and isolated centrosomal P4.1-associated protein (CPAP) as a candidate for a RelA-associating partner. Glutathione S-transferase pull-down assays and co-immunoprecipitation experiments followed by Western blotting also showed assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…CEP65 has been identified to contain eight coiled-coil domains (3), which are involved in the mediation of protein-protein interactions (32). To date, the spectrum of CEP65-binding proteins is unclear, while several other centrosomal proteins have been found to be involved in the regulation of gene transcription (5,33). For instance, NPHP6/CEP290 is physically associated with activating transcription factor 4 (ATF4), which may synergistically regulate renal development (5).…”
Section: Discussionmentioning
confidence: 99%
“…CEP65 has been identified to contain eight coiled-coil domains (3), which are involved in the mediation of protein-protein interactions (32). To date, the spectrum of CEP65-binding proteins is unclear, while several other centrosomal proteins have been found to be involved in the regulation of gene transcription (5,33). For instance, NPHP6/CEP290 is physically associated with activating transcription factor 4 (ATF4), which may synergistically regulate renal development (5).…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR was performed as described previously (45) using a one-step RNA PCR kit (Takara). Primers for amplifying each gene were as follows: 5′-CTCTGAGGTTTAGCATTTCA-3′ and 5′-CTCCAGGTCCAAAATGAATA-3′ for cIAP ; 5′-GCAGATTTATCAACGGCTTT-3′ and 5′-CAGTTTTCCACCACAACAAA-3′ for XIAP ; 5′-TAGCCAACATGTCCTCACAGAC-3′ and 5′-TCTTCTACCACTGGTTTCATGC-3′ for ISG56 ; 5′-GCCTTTTCATCCAAATGGAATTC-3′ and 5′-GAAATCTGTTCTGGGCTCATG-3′ for PKR ; and 5′-CCATGGAGAAGGCTGGGG-3′ and 5′-CAAAGTTGTCATGGATGACC-3′ for GAPDH , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The hydrophobic regions in CENPJ form a stripe that winds around alpha-helix, which is capable of interacting with the hydrophobic residues of a second molecule to form a coiled-coil structure (Cohen and Parry 1986;Hung et al 2000). Several recent reports have shown that CENPJ contributes in the RelA, STAT5 and NF-kB mediated transcription, but these seem less likely to influence neurogenesis (Peng et al 2002;Koyanagi et al 2005;Bond and Woods 2006).…”
Section: Discussionmentioning
confidence: 99%